Effects of Authoritative Parenting Style and Social Support on Prosocial Behaviors with Mediating Effect of Empathy in Higher Education - Chitayasothorn, Dulaya (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The Purposes of this research were to study the effect of authoritative parenting style and social support on prosocial behavior with the mediating effect of empathy. Participants were 500 undergraduate students, who completed a questionnaire on measures of authoritative parenting styles, social support, prosocial behavior and empathy. The results are as follows: authoritative parenting styles have no effects on prosocial behavior, social support has an effect on prosocial behavior (p < .01), while empathy has no mediating effect between authoritative parenting styles and prosocial behavior, and no mediating effect between social support and prosocial behavior.